Molecular Characterization of the Circulating Strains of Vibrio cholerae during 2010 Cholera Outbreak in Nigeria (Journal of Health, Population and Nutrition, 2013)
This study aimed at characterizing the phenotypic and toxigenic status of circulating strains of cholera during outbreaks in Nigeria, employing molecular typing techniques. Two hundred and one samples of rectal swabs, stool, vomitus, water (from the well, borehole, sachet, stream, and tap) and disinfectants (sodium hypochlorite) were collected from three states in the country. The samples were inoculated on thiosulphate-citrate bile salt-sucrose (TCBS), Cary-Blair transport medium and smeared on glass slides for direct examination. The Vibrio cholerae isolates were serotyped, biotyped, and characterized using PCR of the cytotoxin gene A (ctxA), wbeO1, and wbfO139 gene primer. Of the 201 samples screened, 96 were positive for V. cholerae O1 (48%), with 69 (72%) positive for ctxA gene. The results from this study showed that the circulating strains of cholera in Nigeria were of Ogawa serotype, also observed in other outbreaks in Nigeria (1991, 1992, and 1996). However, the strains were of the Classical biotype and were mainly (72%) ctxA gene-positive. This current investigation has confirmed the production of cholera toxin by the circulating strains, and this could be harnessed for possible cholera vaccine production in Nigeria. J HEALTH POPUL NUTR 2013 Jun; 31(2): 178-184 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16381